Indirect contacts between Danish pig farms – what are the frequencies and risk-reducing measures, and how can they be used in simulation models? - Mette Fertner; Beate Conrady; Anne Sax Røgind; Elisabeth Okholm Nielsen; Anette Boklund (Acta Veterinaria Scandinavica)
Abstract Background Information on indirect contacts (e.g. contact with visitors and non-porcine species on farms, shared staff and equipment, contact with trucks) is often poorly recorded even though it constitutes a risk in terms of disease transmission. The aim of the present study was to quantify the number of indirect contacts and associated biosecurity measures in Danish pig herds. A questionnaire survey was conducted among both veterinarians and pig producers in Denmark during 2022–2023. The veterinary questionnaire resulted in 143 answers, representing the Veterinary Health Advisory Service contracts for 53% of non-hobby pig farms. The questionnaire for the pig producers resulted in 373 valid responses and a final response rate of 18%. The results from the veterinary questionnaire provide information on veterinary contacts between pig farms and also estimates on the agreement between registration data and real-life observations. Results The questionnaire for veterinarians stated that the majority of veterinarians specialized within pig practice would visit > 3 pig farms per day, with pig farms being located with an average distance between the farms of 15 km. The veterinarians presumed wind, movement of pigs and trucks transporting pigs to be the main routes of PRRS infection. The questionnaire for pig producers provides updated data on indirect contacts (e.g. contact with visitors and non-porcine species on farms, sharing of staff and equipment, procedures for purchase/delivery of pigs and contact with trucks) stratified in terms of farm type and production type. Among respondents, 10% of the pig producers shared staff, while 2% shared equipment (washing robots) with other farms, excluding farms in a joint operation. When purchasing gilts, 70% of the participating pig producers introduced gilts in line with recommendations for strict quarantine for a minimum of 42 days. The delivery of the pigs varied, depending on the type of pigs being delivered: finishers were typically delivered for slaughter through delivery facilities into a (usually empty) slaughterhouse truck, while sows for slaughter were typically delivered by means of a delivery truck offsite into a slaughterhouse truck (usually with other pigs on board). Conclusion Since the inclusion of indirect contacts in disease spread models relies on valid data, the present study provided valuable data regarding the frequencies and biosecurity measures of indirect contacts between Danish pig herds, which may be useful in the parametrization of computational epidemiological models.